Fibre-Reinforced Generalized Anisotropic Thick Plate with Initial Stress under the Influence of Fractional Thermoelasticity Theory (Advances in Applied Mathematics and Mechanics, 2018)
In the present work concentrated on the two-dimensional problem of generalizedthermoelasticity for a fiber-reinforced anisotropic thick plate under initial stress.Using generalized thermoelasticity theory with fractional order heat conduction, theproblem has been solved by a normal mode analysis. The effect of hydrostatic initialstresses and fractional order parameter is shown graphically on the distributions ofthe temperature, displacement and thermal stress components. It is found from thegraphs that the initial stress and the fractional parameter significantly influence thevarieties of field amounts.